Analisis Penggunaan Media Komunikasi Pembelajaran Google Class Room (GCR) Berbasis Teknologi - Dailami Dailami; Sri Rahmayanti (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2024)
The study aims to analyze the use of technology-based Goggle Class Room (GCR) communication media. Qualitative descriptive research method technique with data collection through questionnaires using google forms. The respondents of this study are students in the third (three) semester of the Management study program, Faculty of Economics, Asahan University for the 2023/2024 Academic Year who took the Business Communication course. The number of 50 respondents, representatives of 5 classes. Taken using purposive sampling technique covering 10 people per class. The results showed that the majority of respondents, 64%, said they "strongly agree" in the use of GCR learning media because it is very practical and efficient because it is used anytime and anywhere, so students can no longer reason if they are late in submitting assignments. GCR is an effective learning medium used by lecturers, as seen in the respondents' answers stating 58% on the criteria "strongly agree" and respondents' answers 86% on the criteria 'strongly agree". The conclusion of this study is that GCR learning media is a technology-based application that facilitates access between lecturers and students to discuss business communication lecture materials.